Peran Kepercayaan Konsumen dan Kualitas Layanan terhadap Kepuasan Pelanggan - Linawati, Igo (Universitas Darwan Ali, 2024)
Service quality become one of the main keys to providing customer satisfaction. Poor service is one of the reasons for the emergence of problems, namely customers running to other services. Sicepat Express in 2021 became the top 3 expedition companies most widely used by online shopping consumers because it has good service quality with a percentage of 13%. However, a mini survey conducted on 10 samples of the Kasongan city community found that consumers using Sicepat Express in Kasongan were disappointed with the Sicepat Express service. This study aims to: (1) determine the effect of service quality on customer satisfaction at Sicepat Express Kasongan City; and (2) effect of customer trust on customer satisfaction. This study uses a quantitative approach with a sample of 100 customers from Sicepat Kasongan City. The method that will be used is the accidental sampling technique with a convenience sampling approach. Data analysis method is by testing the validity and reliability with SPSS 22 application analysis tools. The results of this study are: (1) the service quality variabel (X1) has a significant effect on the customer satisfaction variabel (Y), and (2) the customer trust variabel (X2) has a significant effect on the customer satisfaction variabel.